(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The Timurid period (14th–15th centuries) transformed Samarkand into one of the leading centers of science in Central Asia. This study analyzes the construction, structure, and scientific achievements of the Mirzo Ulugh Beg Observatory, as well as its contribution to fifteenth-century astronomy. Based on historical sources, archaeological evidence, and modern research, the paper examines the significance of the Zij-i Guragani and highlights the remarkable accuracy achieved in astronomical observations without the use of telescopes.